DIGITAL RISK MAPPING UNTUK PENGUATAN MANAJEMEN RISIKO K3 DI PESANTREN AL MIZAN LAMONGAN - Laely Ufiz Tsani Sugiyana; Izza Eka Ningrum; Nadiya Istighfaara; Maharani Nusara Ardhi; Eko Ari Bowo; Herlambang Syafian Arintra; Finaty Ahsanah; Riyanto Riyanto; Muhammad Amiruddin Najhan; Wira Rahmawan; Abyan Rasyad Abdul Hafizd; Ivandi Rizqi Saputra (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2025)
As a boarding school-based educational environment with intense activities, Islamic boarding schools have high potential risks in terms of safety, health, and the environment, thus requiring systematic and integrated risk management. This Community Service activity aims to empower students and managers of Al Mizan Islamic Boarding School in Lamongan through the application of participatory and digital technology-based Digital Risk Mapping. The method used is a participatory approach through focus group discussions, counseling and training on hazard identification and risk analysis, as well as assistance in compiling a digital risk map. The results of the activity show an increase in the knowledge and awareness of students and boarding school administrators regarding K3 and environmental risk management. Additionally, an OSH risk map for the boarding school environment was developed, which includes high-risk areas, types of hazards, and risk levels, and is ready to be used as a basis for risk control and emergency preparedness. It was concluded that this program contributes to building a risk-aware culture and strengthening the internal capacity of the boarding school towards more systematic and sustainable risk management.